ANALISIS SEMIOTIKA PESAN DAKWAH DALAM FILM “TITISAN SUCI” PADA CHANNEL YOUTUBE TARBIAH SENTAP (Fakultas Dakwah dan Komunikasi, 2021)
The implication of this research is that movie lovers on the youtube site, the film Titisan Suci on the Tarbiah Sentap youtube channel is recommended by researchers to film lovers because there is interesting packaging and content of Da'wah messages that are suggested to be noticed by movie lovers on the youtube site. In answering these problems, the authors use qualitative research methods using the mass media approach and Da'wah media, the data sources of this research are primary and secondary data. The method of data collection is carried out through the stages of observation (observation), documentation, and library research (library research). Then the data analysis method is carried out by analyzing using Roland Barthes' semiotic theory in the form of connotation, denotation, and myth meaning. The results of this study are 1) The packaging of Da'wah messages in the sacred incarnation film consists of Da'wah aspects, namely faith, sharia, and morals. 2) There is a meaning of the message of Da'wah from the aspect of aqidah, namely surrendering to Allah, and only to Allah, humans ask for forgiveness, from the Sharia aspect, namely establishing prayers, and reading the holy verses of the Koran while from the aspect of Akhlaq it describes Akhlaq to oneself, fellow humans, all His creatures and to Allah SWT.